The use of cough and cold medicines among filipino households of Barangay Tandang Sora, Quezon City - De Lara, Anne Feliza M.; Guico, Carla Solina O.; So, Tricia Charmaine P.
The most common conditions treated by over-the -counter (OCT) medications are coughs and colds. Although proven safe for use, common cough and colds medications present risks if misused among children, especially in the practice of self-medication. This descriptive research aimed to evaluate the current self-medication practice to alleviate cough and colds symptoms among households in Barangay Tandang Sora, Quezon City, by describing the commonly used medications, current practice based on the internal environment (symptoms experienced of child, medications used for symptoms, frequency, and duration of use) and external environment (demographics, sources of information, and sources of drugs) of the household. Correctness of practice was determine by comparing the actual use with the recommended use based on drug literature. A survey on 100 respondents using a structured questionnaire as tool was conducted to obtain such information. The results showed that all of the respondents practiced self-medication. The most common medications used were paracetamol, carbocisteine, and phenylephrine/chlorphenamine/paracetamol combination. Prescription drugs including antibiotics were also used to treat cough and colds. In terms of the dosage form and dose, liquid formulations and pediatric formulations were preferred. Although the self-medication practice among the households can overall be deemed as appropriate, some areas of concern in the self-medication practice are inappropriate use of certain cough medications and the use of past prescriptions. Empowerment by pharmacists can help in improving the current practice of self-medication. Modifications on the population, research tool and the use of correlational studies can guide subsequent research.
Undergraduate Thesis (BS in Pharmacy)--University of the Philippines Manila, 2015
Keywords: Antibiotics; Self-medication.